Quantitative Usage of Demonstrative Pronouns in Translated and Non-Translated Texts - Bartkutė, Darija (Respectus Philologicus, 2018)
[full article and abstract in Lithuanian; abstract in English] The article aims to estimate the distribution of demonstrative pronouns in the translated and nontranslated Lithuanian text as compared to the English original. The quantitative method and contrastive analysis based on the triangulation of data sources are used to reveal whether demonstrative pronouns show different distribution patterns in the English original and Lithuanian translation compared to the translated and non-translated Lithuanian text. The research material was collected from Harry Potter and the Goblet of Fire by J. K. Rowling and a fantasy novel Hour of the Wolf by A. Tapinas. The preferences identified did not indicate significant differences in the tendencies for the use of demonstrative pronouns in the translated and non-translated text of Lithuanian fiction but revealed significant cross-linguistic contrasts in the quantitative use of demonstratives. It was therefore presumed that there was no communicative difference between the translated and non-translated Lithuanian fictional text due to the genre and language conventions for the use of deictics and that the Lithuanian text demonstrated a preference for a more pronounced pragmatic explicitness than the English language text.